The Structure of English Verbs - Sisilia Halimi (Journal of English Language and Culture, 2017)
This paper explores the structure of English verbs, with particular attention to tense. Before discussing English tenses, the structure and systems of English verb phrase will be explained. After this exploration, some features of English tenses which are found to be the most difficult for Indonesian learners and the implication for teaching them will be discussed. Key words:  English verbs, English verb phrase, English tenses, Indonesian learners